2016
DOI: 10.1590/0103-6440201600708
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Morphology Affects Bite Force in Patients with Painful Temporomandibular Disorders

Abstract: Craniofacial morphology affects masticatory performance in healthy dentate subjects, but little is known about its effects in patients with painful temporomandibular disorders (TMDs). Forty-eight female patients (mean age of 28±5.8 years) with painful TMDs underwent lateral cephalometric radiography. Using Ricketts' cephalometric analysis and the Vert method, subjects were assigned to three groups according to their craniofacial morphology: brachyfacial (n=22), mesofacial (n=13), and dolichofacial (n=13). Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Also, Ow et al found that patients with TMD demonstrate significant variations in the values of MBF at multiple repeated registrations, which indicates the loss of sensory acuity in regulating the masticatory muscle function 27 . Bavia et al reported that in patients with different craniofacial morphology and painful TMD, the maximum bite force was reduced, but this did not affect the mastication performance of the respondents 28 . However, the results of some studies show that there is no change observed in MBF in patients suffering from TMD (ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Ow et al found that patients with TMD demonstrate significant variations in the values of MBF at multiple repeated registrations, which indicates the loss of sensory acuity in regulating the masticatory muscle function 27 . Bavia et al reported that in patients with different craniofacial morphology and painful TMD, the maximum bite force was reduced, but this did not affect the mastication performance of the respondents 28 . However, the results of some studies show that there is no change observed in MBF in patients suffering from TMD (ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of some studies show that there is no change observed in MBF in patients suffering from TMD (ref. 12,28 ). These findings are probably the result of different measurement techniques applied.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the maximum bite force of each group was significantly different. It is speculated that the craniofacial shape affects the maximum bite force (Bavia et al, 2016).…”
Section: Piezoresistive Transducermentioning
confidence: 99%
“…It is of note that could not been observed in the present investigation any difference in bite force between genders. Reports of muscle pain with a reduction of bite force in this study suggested that the painful symptoms impede individuals from exercising the maximal bite force ( 33 ).…”
Section: Discussionmentioning
confidence: 67%